EFFECTS OF SCARIFICATION AND NUTRIENT MINERAL CONCENTRATIONS ON THE IN VITROGERMINATION OF SENNA MACRANTHERA (COLLAD.) H. S. IRWIN & BARNEBY SEEDS - Faria, D. V.; Lima, A. B. P.; Silva, Nina Claudia Barboza da (Emirates Journal of Food and Agriculture, 2017)
Senna macranthera is a tree species used in the recovery of degraded ecosystems whose wood is also used in carpentry and for cooking. Extracts of its leaves and seeds have shown potential pharmacological activities. The seeds demonstrate dormancy, which affects seedling production and the commercial propagation of the trees. We evaluated different methods for overcoming seed dormancy and the effects of nutrient media concentrations and light on the in vitro germination of S. macranthera. Seeds were subjected to chemical scarification with H2SO4 or mechanical scarification using sandpaper. Non-scarified seeds were used as control. Seeds were inoculated into test tubes containing MS, MS ½, or WPM medium and kept in growth rooms under a 16L:8D photoperiod or in total darkness. Scarification treatments promoted greater germination percentages than controls under all germination conditions tested. Sixty days after inoculation, the seedlings germinated from scarified seeds had greater root and shoot lengths than those of the controls, regardless of the culture medium used. It can be concluded that the physical methods used for overcoming dormancy are necessary and effective in promoting in vitro germination and subsequent seedling growth.